2020
DOI: 10.5114/aoms.2019.86101
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of tumor-infiltrating lymphocytes in gastric cancer: a meta-analysis and experimental validation

Abstract: Introduction: We performed a meta-analysis and an experimental validation to investigate the association between tumor infiltrating lymphocytes (TILs) and the outcome of gastric cancer (GC) patients to provide prognostic indicators for clinical practice. Material and methods: The relative literature of TILs in tumor tissue from patients with gastric cancer was searched from PubMed, Embase, NIH databases, from April 2000 to 31 December 2016. Studies on the prognostic value of TILs as CD3+, CD4+, CD8+, GrB+, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 54 publications
(94 reference statements)
0
22
0
Order By: Relevance
“…Most studies of TILs (including CD8+ T cells) and B7-H3 in GC are carried out on Asian cohorts. According to their meta-analyses, higher intratumour CD8 expression is associated with an improved overall survival [ 2 , 12 ]. Distinct tumour immunity signatures between Asian and non-Asian GCs have been found, including higher expression of CD8 in Western GCs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of TILs (including CD8+ T cells) and B7-H3 in GC are carried out on Asian cohorts. According to their meta-analyses, higher intratumour CD8 expression is associated with an improved overall survival [ 2 , 12 ]. Distinct tumour immunity signatures between Asian and non-Asian GCs have been found, including higher expression of CD8 in Western GCs [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…They are able to recognize tumour-specific antigens and destroy cancer cells by perforin and granzyme-mediated apoptosis. Studies show that a higher amount of CD8+ T cells in the tumour is associated with better prognosis in gastric cancer (GC) [ 2 , 3 ]. However, during cancer progression they become inactivated due to the immunosuppressive nature of TIME.…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, chemotherapy leads to the death of tumor cells, which may increase antigen presentation (62,78), while other research has found that neoadjuvant chemotherapy (NACT) also induces upregulated levels of CD8+, PD-1, and PD-L1 (79,80). In addition, CD45RO-positive T cells seem to express more interferon-Îł (IFN-Îł), and IFN-Îł are likely to induce local immune activation (81) and the absence of immunosuppressive elements like FOXP3+ T cells (82). In our case, neoadjuvant chemotherapy may alter the tumor microenvironment, so that the patient could benefit from immunotherapy and achieved pCR.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of CD4 T cells, macrophage M2 and monocyte were high in the high-risk group, which seemed to be an explanation for the prognostic power of the signature. It is known that CD4+ T cells are essential organizers of cell-mediated immunity, participating in every stage of the immune response [ 20 ]. Naive CD4+ T cells can be induced to differentiate to specific lineages according to the local cytokine milieu, towards Th1, Th2, Th17 and Treg and Th17 cells with both anti-tumor and pro-tumor functions in different cancers [ 20 ].…”
Section: Discussionmentioning
confidence: 99%